2020
DOI: 10.26452/ijrps.v11ispl3.3415
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of parents willingness to take up fluoride treatment for their children, the gender differences and common age of acceptance - A retrospective study

Abstract: Fluoride used as a chemotherapeutic agent for caries prevention has been widely researched and documented. The change in the prevalence of caries and advent of different fluoride formulations along with the desire to maximize the benefits and minimise the side effects has led to evoking guidelines for its use. Fluoride varnish, which is one of the most important materials to prevent early childhood caries, is easy to apply and well-tolerated by children. The study aims in assessing the perception of parents to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…From the results, it was reported that the mean age of the study for children undergoing topical fluoride treatment was five years. This was in keeping with the study by Ramya et al, [16]. It is due to fluoride being prescribed for children from ages 5 to 17 years.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…From the results, it was reported that the mean age of the study for children undergoing topical fluoride treatment was five years. This was in keeping with the study by Ramya et al, [16]. It is due to fluoride being prescribed for children from ages 5 to 17 years.…”
Section: Resultssupporting
confidence: 89%
“…In addition to its established cariostatic effect, fluoride is a hazardous substance when excessive intake occurs by ingestion of a large dose. It provokes effects ranging from nausea, vomiting, abdominal pain to even death [16]. Lower doses taken chronically can affect the developing mineralised dental tissues, thus resulting in dental fluorosis, and hypomineralization of enamel clinically, characterised by opacity, pitting or staining.…”
Section: Open Accessmentioning
confidence: 99%